Ion beam forming dynamics in an injector taking into account a plasma boundary - Demchenko, P.O.; Shulika, M.G. (Вопросы атомной науки и техники, 2001)
The developed program code taking into account a shape and position of an emitting plasma boundary had been used to examine a deuterium beam forming in an injector. It has been shown that the beams formed by a three-electrode ion optical system have a complex density distribution in a beam phase space. For the narrow current range it is possible to have a beam crossover at the injector output with a radius of 1mm and divergence less then 20 mrad.